Análisis multitemporal del cambio de coberturas en la cuenca del Lago Guamuez (Pasto, Nariño) durante el periodo 1986-2016 (2023)
The present work aims to calculate the change in coverage in a specific geographic area and within given time limits, using landsat satellite images. The work employs a methodology that begins with the download of images, which will be processed with specialized programs such as Erdas, - Arcgis - ENVI. Subsequently, a supervised classification of these images was carried out under the GEOBIA object-oriented paradigm in order to characterize the land cover present in each of the years analyzed. It was found that there was a loss of forest cover of approximately 4.6%, which had a transition to bare soil, and grass had a transition of approximately 21.8% to bare soil for the years analyzed